Strategic Analysis of the Organization’s Vision and Mission in Improving Company Performance and Competitiveness - Hermawan, Herman; Ibrahim, Syufriadi; Augustriandi; Pahala, Indra; Handaru, Agung Wahyu (Jurnal Informatika Ekonomi Bisnis, 2025)
This research aims to analyze the role of organizational vision and mission in improving company performance and competitiveness. Using the literature study method, this research examines various relevant sources to identify how vision and mission can serve as strategic guides in decision-making. The analysis shows that a clear vision and well-defined mission contribute to the creation of a strong organizational culture, increased employee motivation, and the development of effective strategies. In addition, this study found that companies that consistently review and update their vision and mission tend to be more adaptive to market changes and able to maintain a competitive advantage. These findings provide important insights for managers and organizational leaders in formulating result-oriented strategies to improve the overall performance of the company in the era of global competition.